OPTIMISME, DUKUNGAN SOSIAL SUAMI, DAN STRES PADA IBU RUMAH TANGGA DAN IBU YANG BERPERAN GANDA DI MASA PANDEMI COVID-19 - Maria Prima Novita; Arthur Huwae (Jurnal Psikohumanika, 2022)
The COVID-19 pandemic has brought mothers to experience additional roles and responsibilities when their children should study from home. This kind of situation causes stress that cannot be controlled and it continues to increase, so it needs internal support (self) and external support (environment) to minimize the level of maternal stress experienced. Following up on this, this study aims to determine the relationship between optimism and husband's social support with the maternal stress level for mothers, and the differences in maternal stress level among housewives and multiple-role mothers during the COVID-19 pandemic. This research used multiple and comparative correlational quantitative. 102 people which consist of 51 housewives and 51 multiple-role mothers participated in this research using the snowball sampling technique. The measurement scale consists of an optimism scale, a husband's social support scale, and a stress scale. The result proved that simultaneous optimism and husband's social support related to the stress that happened to the mothers during the COVID-19 pandemic as well as specifically each independent variable related to the stress that happened in mothers during the COVID-19 pandemic. Comparatively, the result proved that there was no stress difference between housewives and multiple-role mothers during the COVID-19 pandemic. Thus, the problem of maternal stress during the COVID-19 pandemic could be handled well since the housewives and multiple-role mothers were able to create moderative optimism and their husbands put high support on them.